Economic growth in dual and mature economies: Revisiting the Pasinetti and neo-Pasinetti theorems - Peter Skott (University of Massachusetts, Department of Economics, 2022)
This paper (i) examines the role of income distribution in the determination of the average saving rate and the growth process in dual and mature economies, and (ii) revisits the Pasinetti and neo-Pasinetti theorems. The profit share may influence saving because of differences in the saving rates across households (the Pasinetti theorem) or because firms retain part of their earnings (the neo-Pasinetti theorem). The two mechanisms are not mutually exclusive, and the alignment between warranted and natural growth rates in mature economies can happen through feedback effects from employment to the distribution of income.
Keywords: E12; E21; O41; 330; Harrod's problems; income distribution; saving rates; Cambridge equation